ANALISIS KECELAKAAN DI JALAN RAYA NGANJUK-MADIUN DENGAN METODE ANGKA EKIVALEN KECELAKAAN DAN UPPER CONTROL LIMIT - A`ini, Hanifa Nur; RA Dinasty Purnomoasri; Nursetyo, Gatot (Jurnal Teknik Sipil dan Arsitektur, 2025)
The Nganjuk-Madiun highway is a national road that connects the provincial capitals of East Java and Central Java. Therefore, the road is quite potential for traffic flow movements that have a fairly high accident rate. This analysis is used to determine and analyze the causal factors, characteristics, locations of accident-prone areas (blackspots), conditions of accident-prone areas (blackspots), and preventive measures that can be taken. The methods used in this analysis are the AEK (Accident Equivalent Number) method and the Upper Control Limit Method. Primary data is data on the geometric condition of the road, while secondary data is the number, time, location, day, class of victims, and type of vehicle obtained from the Nganjuk Police Traffic Unit in 2019 - 2023. The results of this study indicate that the characteristics of accidents based on the location of the most segments occurred in 2019 in segment 1 as many as 15, based on the time of the incident, namely at 06.01-07.00 WIB as many as 12 incidents, based on the class of victims, namely minor injuries (LR) as many as 93 victims, based on the type of vehicle, namely motorcycles as many as 63. Accident-prone areas on the Nganjuk-Madiun highway, Bagor District for 5 years (2019-2023) are in segment 3 with an AEK value of 314 and a UCL value of 302.68. Efforts that can be made to prevent accidents include installing traffic warning signs, adding road markings, repairing street lights, and adding road noise tape.